Did judge dismiss student's false imprisonment claim?. Issue 4 (13th July 2021) - Lyerly, Eric
Abstract : St. John's University police asked a student for a meeting in connection with a reckless driving incident on campus. When the student appeared, the interviewing officer told him there was a video showing he was the reckless driver. The student denied he was the one driving. He informed the officers the female student falsely accused him to protect her boyfriend.